Polyaniline − carbon nanohorn composites as thermoelectric materials. Issue 12 (7th April 2017) - Famengo, Alessia; Ferrario, Alberto; Boldrini, Stefano; Battiston, Simone; Fiameni, Stefania; Pagura, Cesare; Fabrizio, Monica
Abstract: Thermoelectric materials can convert heat into electricity when a temperature gradient is present. The investigation of conductive polymers such as polyaniline (PANI) and poly(3, 4‐ethylenedioxythiophene) as active materials for thermoelectric generators in the room temperature range is gaining interest because of several key advantages offered by these materials. The relative ease of solution processing, their mechanical stability and flexibility together with low density and low thermal conductivity make conductive polymers suitable for integration in a thermoelectric generator. Polymers offer remarkably low thermal conductivity values but modest Seebeck coefficient and electrical conductivity. In this work, polymer/inorganic nanocomposites of PANI with carbon particles such as single wall carbon nanohorns (SWCNHs) were prepared via solution mixing of the precursors in order to increase the electrical conductivity by means of polymer matrix/nanohorn electronic junctions. The electrical conductivity and Seebeck coefficient were estimated on PANI/SWCNH films and pressed pellets and through‐plane thermal conductivity was determined on films. The thermal stability of PANI/SWCNH composites was evaluated by means of TGA/DSC coupled with residual gas analysis. It was found that a proper concentration of SWCNHs in PANI−(+/−)‐camphor‐10‐sulfonic acid (CSA) film was effective in increasing the electrical conductivity without decreasing the Seebeck coefficient. © 2017 Society of Chemical Industry Abstract : Polymer/inorganic nanocomposites of PANI with single wall carbon nanohorns (SWCNHs) were prepared as active materials for thermoelectric generators. The polymer matrix/SWCNH electronic junction allows an increase of electrical conductivity.